Integrated Evaluation of Innovative Development of the New EU Member States and Other EU Countries - Dovgal, Olena; Goncharenko, Nataliia; Karp, Viktoriia; Revyakin, Georgij (Comparative Economic Research. Central and Eastern Europe, 2022)
This study investigates the problem of estimating various aspects and qualitative features of innovative development. A new methodological approach to comprehensively assessing the polystructural nature of modern innovative development in the new EU member states and other EU countries is proposed, which allows us to identify growth points and promising areas to increase their innovative development. Aspects such as information adaptability, innovative orientation, and synergetic efficiency are considered. The analysis is based on a logical evaluation of indicators that characterize science, technology, and the digital society in accordance with the data presented in the public domain, from which the main indicators that characterize these three aspects of the EU’s innovative development were selected. According to the algorithm of the matrix method for the new EU member states and other EU countries, the maximum (reference) value was chosen for each indicator and the coefficient of compliance with the reference value of a particular indicator was calculated. As a result, integrated indicators of assessing information adaptability, innovative orientation, and synergetic efficiency and the integrated indicator of innovative development of the EU countries were calculated, which allowed us to rate them. The innovative development of the economies of the EU countries differs significantly in some indicators and aspects. The assessment and comparison of innovative development at the national level depends on many factors but is primarily determined by public policy and national priorities of a particular country. That is why a promising direction of increasing the innovative development of all EU countries should be, first of all, the further development of their mutual exchange of technologies based on the existing integration scientific and technical potential.